EFEKTIVITAS TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION DAN MUSCLE ENERGY TECHNIQUE TERHADAP PERUBAHAN NYERI MYOFASCIAL TRIGGER POINTS MUSCULUS UPPER TRAPEZIUS: Efficacy of Transcutaneous Electrical Nerve Stimulation and Muscle Energy Technique on Myofascial Trigger Point Pain in the Upper Trapezius - Hasnia Ahmad; Abdullah Tamir; Siti Nurul Fajriah; Fahrul Islam; Hasbiah (Media Fisioterapi Politeknik Kesehatan Makassar, 2026)
Myofascial Trigger Point in the Upper Trapezius muscle is a musculoskeletal disorder characterized by a hyperirritable spot within a skeletal muscle, presenting as a hypersensitive nodule located in a taut band. This nodule is painful upon compression and can cause referred pain.This study aimed to determine the pain intensity of myofascial trigger points in the upper trapezius muscle before and after the application of Transcutaneous Electrical Nerve Stimulation (TENS) and Muscle Energy Technique (MET), as well as to ascertain the magnitude of the effect of TENS and MET on changes in myofascial trigger point pain in the upper trapezius.The research employed a Pre-Experimental design with a "One-Group Pretest-Posttest Design." The study results indicated that the pain intensity of myofascial trigger points in the upper trapezius muscle before TENS and MET administration was in the severe and moderate pain categories. Conversely, the pain intensity after TENS and MET administration was in the mild and moderate pain categories.Furthermore, the results of the Wilcoxon test showed a p-value of < α (p: 0.001 < α 0.05), indicating a significant reduction in pain. The conclusion of this study is that TENS and MET are effective in reducing pain in cases of upper trapezius myofascial trigger points. Kata Kunci : Myofascial Trigger Point (MTrP), Muscle Energy Technique (MET), Transcutaneous Electrical Nerve Stimulation (TENS), Nyeri, Numeric Rating Scale (NRS) ABSTRAK Myofascial Trigger Point Musculus Upper Trapezius adalah gangguan muskloskeletal dimana di tandai dengan adanya titik hiperiritabilitas di otot skeletal yang terdapat nodul hipersensitif yang terletak pada taut band. Nodul tersebut terasa nyeri saat ditekan dan dapat menimbulkan nyeri tekan yang menjalar. Penelitian ini bertujuan untuk mengetahui tingkat nyeri myofascial trigger point musculus upper trapezius sebelum dan sesudah diberikan Transcutaneous Electrical Nerve Stimulation (TENS) dan Muscle Energy Technique (MET) serta mengetahui seberapa besar pengaruh pemberian TENS dan MET terhadap perubahan nyeri myofascial trigger points musculus upper trapezius. Metode penelitian adalah Pre-Experimental dengan desain “One Groups Pretest-Posttest Design. Hasil penelitian diperoleh intensitas nyeri myofascial trigger points musculus upper trapezius sebelum pemberian TENS dan MET berada pada kategori nyeri berat dan nyeri sedang. Sedangkan Intensitas nyeri myofascial trigger points musculus upper trapezius setelah pemberian TENS dan MET berada pada kategori nyeri ringan, dan nyeri sedang. Kemudian hasil uji Wilcoxon p < α artinya p : 0,001 < α 0,05 menunjukkan pengurangan nyeri secara signifikan. Kesimpulan penelitian ini adalah TENS dan MET efektif terhadap penurunan nyeri pada kasus myofascial trigger points upper trapezius. Keywords : Myofascial Trigger Point (MTrP), Muscle Energy Technique (MET), Transcutaneous Electrical Nerve Stimulation (TENS), Nyeri, Numeric Rating Scale (NRS)